Galectin-2 Induces a Proinflammatory, Anti-Arteriogenic Phenotype in Monocytes and Macrophages - Yıldırım, Cansu; Vogel, Daphne Y. S.; Hollander, Maurits R.; Baggen, Josefien M.; Fontijn, Ruud D.; Nieuwenhuis, Sylvia; Haverkamp, Anouk; de Vries, Margreet R.; Quax, Paul H. A.; Garcia-Vallejo, Juan J.; van der Laan, Anja M.; Dijkstra, Christine D.; et al. (PLOS ONE, 2015)
Galectin-2 is a monocyte-expressed carbohydrate-binding lectin, for which increased expression is genetically determined and associated with decreased collateral arteriogenesis in obstructive coronary artery disease patients. The inhibiting effect of galectin-2 on arteriogenesis was confirmed in vivo, but the mechanism is largely unknown. In this study we aimed to explore the effects of galectin-2 on monocyte/macrophage phenotype in vitro and vivo, and to identify the receptor by which galectin-2 exerts these effects. We now show that the binding of galectin-2 to different circulating human monocyte subsets is dependent on monocyte surface expression levels of CD14. The high affinity binding is blocked by an anti-CD14 antibody but not by carbohydrates, indicating a specific protein-protein interaction. Galectin-2 binding to human monocytes modulated their transcriptome by inducing proinflammatory cytokines and inhibiting pro-arteriogenic factors, while attenuating monocyte migration. Using specific knock-out mice, we show that galectin-2 acts through the CD14/toll-like receptor (TLR)-4 pathway. Furthermore, galectin-2 skews human macrophages to a M1-like proinflammatory phenotype, characterized by a reduced motility and expression of an anti-arteriogenic cytokine/growth factor repertoire. This is accompanied by a switch in surface protein expression to CD40-high and CD206-low (M1). In a murine model we show that galectin-2 administration, known to attenuate arteriogenesis, leads to increased numbers of CD40-positive (M1) and reduced numbers of CD206-positive (M2) macrophages surrounding actively remodeling collateral arteries. In conclusion galectin-2 is the first endogenous CD14/TLR4 ligand that induces a proinflammatory, non-arteriogenic phenotype in monocytes/macrophages. Interference with CD14-Galectin-2 interaction may provide a new intervention strategy to stimulate growth of collateral arteries in genetically compromised cardiovascular patients.